2019
DOI: 10.1186/s12935-019-1060-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-100-3p inhibits cell proliferation and induces apoptosis in human gastric cancer through targeting to BMPR2

Abstract: Background: miR-100 has been reported to closely associate with gastric cancer (GC) initiation and progression. However, the underlying mechanism of miR-100-3p in GC is still largely unclear. In this study, we intend to study how miR-100-3p regulates GC malignancy. Methods: The expression levels of miR-100-3p in vitro (GES-1 and GC cell lines) and in vivo (cancerous and normal gastric tissues) were examined by quantitative real-time PCR (qRT-PCR). MTT and PE/Annexin V analyses were responsible for measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Controversial reports exist about the role of miR‐99 family members in cancer progression. MiR‐99a is often found to be downregulated in GC tissues (Peng et al, 2019). Cao et al (2018) also showed that out of 38 GC tissues, miR‐100 was downregulated in 30 cases and low levels of miR‐100 correlated with poor disease prognosis.…”
Section: Mir‐99 Family Members In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Controversial reports exist about the role of miR‐99 family members in cancer progression. MiR‐99a is often found to be downregulated in GC tissues (Peng et al, 2019). Cao et al (2018) also showed that out of 38 GC tissues, miR‐100 was downregulated in 30 cases and low levels of miR‐100 correlated with poor disease prognosis.…”
Section: Mir‐99 Family Members In Cancersmentioning
confidence: 99%
“…MiR‐99a and miR‐99b were reported to target IGF‐1R and thereby inhibit cell proliferation (Wang, Zhao, et al, 2018; Xu et al, 2019). The tumor suppressor role of miR‐99a can also be achieved via suppression of bone morphogenetic protein receptor 2 (BMPR2) (Peng et al, 2019). The oncogenic lncRNA HAGLROS was also shown to titrate the level of free miR‐100 in GC cells, indicating the role of miR‐100 as a TSmiR (Chen et al, 2018).…”
Section: Mir‐99 Family Members In Cancersmentioning
confidence: 99%
“…(G) Proliferation and invasion assays in SW780 cells after overexpression of miR-3127. *P < 0.05. performed as previously reported (Peng et al, 2019). In brief, T24 cells were infected by miR-3127-overexpression lentiviral vector or control vector, and SW780 cells were infected by miR-3127sponge lentiviral vector or control vector.…”
Section: Lentiviral Transfectionmentioning
confidence: 99%
“…By comparing the expression levels of miRNAs between 0.5% FBS and 10% FBS in human Sertoli cells, we revealed that miR-100-3p was enhanced by 10% FBS, as demonstrated by miRNA microarray and verified by real-time qPCR. MiR-100-3p has been shown to control the proliferation and the apoptosis of human gastric cancer cells via binding to bone morphogenic protein type 2 receptor (BMPR2) ( Peng et al, 2019 ), and it may be involved in producing interleukin (IL)-8 and IL-1β in mesangial cells ( Liang et al, 2016 ). In this study, we have shown that miR-100-3p stimulates human Sertoli cell proliferation and DNA synthesis, as determined by CCK-8 assay, PCNA expression, and EdU incorporation assay.…”
Section: Discussionmentioning
confidence: 99%